(3GdcGajs - (3Gdcdjfj, GdQGRj, GdSdSdj, GdHZOGOj, CHh LYaQ, eMeO Hf jYbhH Hf ESMGb, J (B329 (3g`s ((3eMeO Hf YHO GdZahQ Hf eQJVis)
(3ChdgG (B:s
(3GdMeO ddg GdeMehO dfYeJg GdeYHhO dbOQJg (B..(3abO ageJ jG CNj eG TchJ ef GUWdGM Cgd OgQfG hJBRQge hSYjge aj YeGQI WQbgG heHGjfJge GdYde hCgdg MJi cGO GdYde eYge Cf jCRQ cdg hjfbWY eQGOg (B...s
(3BNQgG (B:s
... (3HGH eMeO Hf jMji Yf CMeO Hf eMeO Hf Ydj Hf GdMce Yf YHO Gdedc Hf (B... (3GdMSf Ydjg GdSdGe bGd SCdJg Yfe GdbQGWjS JLJeY gd JMQb HGdfGQ ajgG TjA ef PcQ Gddg JYGdi bGd dG JZSd HGdeGA (B... (3Yf CHj GdMSf ehSi Ydjg GdSdGe aj GdXghQ GdJj ajgG PcQ Gddg YR hLd bGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/145s
(3GdPQjYI (B17/96s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs